Medical Response to Terrorism : Preparedness and Clinical Practice. - Keyes, Daniel C. (Wolters Kluwer Health, 2004)
This comprehensive reference provides all the information emergency departments and personnel need to prepare for and respond to terrorist events. The first section covers all agents potentially used in terrorist attacks-chemical, biologic, toxicologic, nuclear, and explosive-in a systematic format that includes background, triage, decontamination, signs and symptoms, medical management, personnel protection, and guidelines for notifying public health networks. Algorithms show when to suspect and how to recognize exposure and detail signs and symptoms and management protocols. The second secti.